Pediatric Anesthesiology Review Clinical Cases for Self-Assessment - Holzman, Robert S.; Mancuso, Thomas J.; Sethna, Navil F.; DiNardo, James A. (Springer New York : Imprint: Springer, 2010)
Based on a program of study developed at the Children's Hospital Boston, Department of Anesthesiology, Perioperative and Pain Medicine, Pediatric Anesthesiology Review: Clinical Cases for Self-Assessment provides essential medical information for the subspecialty of pediatric anesthesiology. Illustrating the broad spectrum of the pediatric anesthesiologist's practice, this book utilizes an interactive question and answer dialogue which imitates the simplicity of conversation and affords the reader high-yield benefits. The case-based approach encourages readers to collaborate with colleagues, improve their oral presentation skills, and prepare for challenging situations by explaining various anesthesia care plans and why specific data are required before and during the care of the pediatric patient. Written by a panel of specialists recognized internationally for their efforts in their respective areas within pediatric anesthesia and examiners for various medical specialty boards including the American Board of Anesthesiology, this self-assessment programmed text for residents, fellows, and clinicians in the field of pediatric anesthesiology offers extremely valuable advice. The ability to explain why, in addition to how, is central to the Children's Hospital Boston program's philosophy, and Pediatric Anesthesiology Review: Clinical Cases for Self-Assessment maintains this ideal in the crafting of this book. An interactive question and answer program is featured on extras.springer.com.